Thiamine supplementation holds neurocognitive benefits for breastfed infants during the first year of life. Issue 1 (7th June 2021) - Measelle, Jeffrey R.; Baldwin, Dare A.; Gallant, Jelisa; Chan, Kathleen; Green, Tim J.; Wieringa, Frank T.; Borath, Mam; Prak, Sophonneary; Hampel, Daniela; Shahab‐Ferdows, Setareh; Allen, Lindsay H.; Kroeun, Hou; et al.
Abstract: Women reliant on mostly rice‐based diets can have inadequate thiamine intake, placing breastfed infants at risk of thiamine deficiency and, in turn, physical and cognitive impairments. We investigated the impact of maternal thiamine supplementation doses on infants' cognitive, motor, and language development across the first year. In this double‐blind, four‐parallel‐arm, randomized controlled trial, healthy mothers of exclusively breastfed newborn infants were recruited in Kampong Thom, Cambodia. At 2 weeks postnatal, women ( n  = 335) were randomized to one of four treatment groups to consume one capsule/day with varying amounts of thiamine for 22 weeks: 0, 1.2, 2.4, and 10 mg. At 2, 12, 24, and 52 weeks of age, infants were assessed with the Mullen Scales of Early Learning (MSEL) and the Caregiver Reported Early Development Instrument (CREDI). Multiple regression and mixed effects modeling suggest that by 6 months of age, the highest maternal thiamine dose (10 mg/day) held significant benefits for infants' language development, but generally not for motor or visual reception development. Despite having achieved standardized scores on the MSEL that approximated U.S. norms by 6 months, infants showed a significant drop relative to these norms in both language domains following trial completion, indicating that nutritional interventions beyond 6 months may be necessary. Abstract : Women reliant on mostly rice‐based diets can have inadequate thiamine intake, placing breastfed infants at risk of thiamine deficiency and, in turn, physical and cognitive impairments. We investigated the impact of maternal thiamine supplementation doses on infants' cognitive, motor, and language development across the first year in a double‐blind, randomized controlled trial in Cambodia that recruited healthy mothers of exclusively breastfed newborn infants.